Insights on the electrochemical performance of indirect internal reforming of biogas into a solid oxide fuel cell. (20th March 2022) - Santoro, Mariarita; Di Bartolomeo, Elisabetta; Luisetto, Igor; Aricò, A.S.; Squadrito, G.; Zignani, S.C.; Lo Faro, M.
Abstract: The use of biogas in solid oxide fuel cells (SOFCs) is a viable approach for generating power from renewables. However, the direct use of dry biogas in SOFCs causes many issues concerning the durability of cells. Currently, the conventional approach consists of the use of an external reformer. Nevertheless, other approaches are possible to reduce the complexity of SOFCs. In this paper, we have investigated an indirect internal dry reforming occurring in the anodic chamber of a SOFC as a viable method to minimise the balance of the plant and simplify the feed management. This approach consisted of coupling a foam coated with NiCo/SDC powder in contact with the anode of a conventional SOFC cell. The electrochemical experiments demonstrated promising performances at 800 °C by feeding dry biogas with a maximum power density above 500 mW cm −2 @ 625 mV. The endurance test revealed a stable behaviour over 500 h. We analysed these results according to the physico-chemical properties of both catalyst and cell. The combined electrochemical and physico-chemical analyses corroborated the occurrence of multistep reactions in the anodic chamber. Graphical abstract: Image, graphical abstract